KONTEKSTUALISASI MAKNA HIJRAH DALAM FENOMENA KABUR SAJA DULU: KAJIAN MA’ANIL HADIS SHAHIH BUKHARI NO.1 DAN NO. 2783 - Raudhatuz Zahra; Abil Ash; Ulfah Zakiyah (DIRAYAH : Jurnal Ilmu Hadis, 2026)
The #KaburAjaDulu phenomenon, which went viral in early 2025, reflects the aspirations of Indonesia’s younger generation to migrate abroad a trend that some groups have framed within the narrative of “hijrah.” This study examines the meaning of hijrah in Sahih Bukhari Hadiths No. 1 and No. 2783 through the ma’anil hadith approach, and then contextualizes it in relation to this phenomenon using three normative principles from the Muqaddimah Qanun Asasi by KH. Hasyim Asy’ari: al-ijtima’ wa al-ittihad, ukhuwah wathaniyah, and hubbul wathan minal iman. The method used is qualitative library research employing the ma’anil hadith approach, along with a study of the commentary Fath al-Bari by Ibn Hajar al-Asqalani. The results of the study show: Sahih Bukhari No. 1 states that the value of all actions, including migration, is determined by one’s intention; No. 2783 states that the obligation of physical hijrah ended after the Conquest of Mecca, and what remains is jihad and intention; and #JustRunAwayFirst is not monolithic; there are three typologies of intention: al-niyyah al-muwafiqah (contribution-oriented), al-niyyah al-mubhamah (ambiguous), and al-niyyah al-musykilah (purely material). This study concludes that the use of the term “hijrah” to encompass the entire spectrum of #KaburAjaDulu is an inappropriate oversimplification, and that the only normative departure that is justified is one oriented toward jihad fi sabilillahactive struggle for the good of the ummah and the nation.